Family and Politics: Untangling the Connections - Breux, Sandra; Mévellec, Anne (Enfances, Familles, Générations)

(untitled) (INRS-UCS, 2024)
Research framework: The relations between family and politics are characterized by their diversity. This variety stems as much from changes in the notion of family as from the contemporary range of forms and types of political commitment. Objectives: This issue seeks to document the various forms taken by the relationship between family and politics. Methodology: The papers in this issue are based on qualitative approaches, enabling a detailed analysis of the often complex interplay between family and politics. Results: The family still appears to be a relevant variable in the analysis of political commitment. While political involvement can take place against the family's wishes, the family can also be the cause of the involvement. Moreover, while the links between family and politics may be plural, they also depend on the nature of the political transmission that takes place within the family circle. Conclusions: The contributions in this issue highlight the fact that the family/political pair cannot do without a reflection on the intertwining of the public and private spheres. Contribution: By re-examining the links between family and politics, this issue builds on previous reflections, while inviting us to discuss gender relations, the importance of affects and the place of intimacy in these relationships.